A Sensitive Chemiluminescent Assay for Aflatoxin B1 - Prasertsilpa, Varipin; Stimson, William H (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this study a chemiluminescent label was substituted for an enzyme marker used in AFB1 ELISA and the minimum detection limits of the direct/modified indirect competitive chemiluminescence immunoassay (CIA), the direct competitive CIA (2 step method), the direct competitive CIA (1 step, 30 min method), and the direct competitive CIA (1 step, 5 min method) were shown to be 10.0, 5.1, 5.6, and 6.8 pg ml-1 respectively. In a direct comparison between different labeling methods but using the same antibodies, the direct competitive CIA (1 step, 5 min method) is superior in sensitivity to the AFB1 ELISA (detection limit 200 pg ml-1). In addition to an increase in sensitivity, the assay time was also reduced. The sensitivity of the assay was not affected by 6.25% (v/v) methanol and required a 1:8 dilution of the peanut extract [using 80% (v/v) methanol as extracting solvent] was required to avoid matrix interference. Keywords: aflatoxin B1, chemiluminescent label, enzyme marker, immunoassay Corresponding author: E-mail: varipin@health.moph.go.th